Analisis Manual Material Handling Dengan Menggunakan Aspek Biomekanika Dan Fisiologi (Studi Kasus: PT. Gujati 59 Utama) - Bagus Pamadi, Anggita, Ir. Etika Muslimah, MT, MM (2017)
PT. Gujati Top 59 is a company engaged in the manufacture of herbal medicine production activities are activities of man and machine. As for Manual Material Handling predominant located in the warehouse of raw materials. The raw material comes every other week with a total load of 25 tons or 500 sacks of sugar. Activities Manual Material Handling in the warehouse of raw materials, namely, employees lifting materials weighing 50kg sugar carried two people, as well as arrange the raw materials to the warehouse measuring approximately 12m2 with a height of 2,5 m arrangement of raw materials and performed by six workers. Thus it seems likely that the risk of muscle injury. One example that is experienced by workers as never felt Nendi 25 years of one of the clerks are often pain in back, pain in the arms and abdominal pain. Hence the need for a review of the research on sugar raw material warehouse to determine the risk yangi experienced workers. As for the study using the concept of Biomechanics and Physiology of Work. Based on the research results can be known tersbut average compressive force (Fc) experienced worker is 6616.80 N. While the average energy consumption experienced workers is 4.77 kcal / Minute. Based on the value of work at risk of muscle injury for Fc> 3400 N, and konumsi energy jobs > 4.7 kcal / Minutes by Recommendations NIOSH